2004
DOI: 10.1080/00016480410016432
|View full text |Cite
|
Sign up to set email alerts
|

Hearing preservation in cochlear implantation for electric acoustic stimulation

Abstract: Preservation of low-frequency hearing in cochlear implantation is possible in patients implanted because of profound high-frequency deafness. With the development of new, more atraumatic electrode designs, preservation of residual hearing should be further improved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
199
3
9

Year Published

2005
2005
2012
2012

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 253 publications
(223 citation statements)
references
References 7 publications
12
199
3
9
Order By: Relevance
“…The electriconly score was 23%, again suggesting a strong synergistic effect for this patient. Gstoettner et al (2004) reported speech results for one patient implanted with a 22mm electrode who improved from 38%-recognition of monosyllables in the acoustic-only mode to 90% with the addition of electric stimulation. Kiefer et al (2005) reported monosyllabic word understanding a group of 11 patients with preserved residual hearing.…”
Section: A+e Results For Speech Presented In Quietmentioning
confidence: 99%
See 2 more Smart Citations
“…The electriconly score was 23%, again suggesting a strong synergistic effect for this patient. Gstoettner et al (2004) reported speech results for one patient implanted with a 22mm electrode who improved from 38%-recognition of monosyllables in the acoustic-only mode to 90% with the addition of electric stimulation. Kiefer et al (2005) reported monosyllabic word understanding a group of 11 patients with preserved residual hearing.…”
Section: A+e Results For Speech Presented In Quietmentioning
confidence: 99%
“…When those three subjects were compared to a group of long-electrode patients (whose speech scores in quiet were matched to the Hybrid subjects), a significant advantage was observed. Gstoettner et al (2004) reported results from one A+E patient tested on sentence recognition in noise. Performance was best for the A+E condition, as compared to either the acoustic-alone or electric-alone condition.…”
Section: A+e Results For Speech Presented In Quietmentioning
confidence: 99%
See 1 more Smart Citation
“…(This ability is nonexistent or almost nil with a unilateral implant, as noted before.) Combined EAS also provides a substantial benefit for listening to speech in quiet, in noise, in competition with another talker, or in competition with a multi-talker babble, compared with either electric stimulation only or acoustic stimulation only (e.g., von Ilberg et al, 1999;Kiefer et al, 2002Kiefer et al, , 2005Gantz and Turner, 2003;Wilson et al, 2003;Gstoettner et al, 2004Gstoettner et al, , 2006Gantz et al, 2005Gantz et al, , 2006Kong et al, 2005;James et al, 2006;Gifford et al, 2007;Dorman et al, 2007;Turner et al, this issue). Indeed, in some cases the score for combined EAS is greater than the sum of the scores for the electric-only and acoustic-only conditions.…”
Section: Two Recent Advancesmentioning
confidence: 99%
“…Indeed, in some cases the score for combined EAS is greater than the sum of the scores for the electric-only and acoustic-only conditions. This has been described as a synergistic effect (e.g., Gstoettner et al, 2004;Wilson et al, 2003). In addition, identification of melodies and reception of musical sounds is greatly improved with combined EAS compared to electric stimulation alone (Gantz et al, 2005;Kong et al, 2005;Gfeller et al, 2006 andGstoettner et al, 2006;Dorman et al, 2007).…”
Section: Two Recent Advancesmentioning
confidence: 99%